Airway commensal bacteria in cystic fibrosis inhibit the growth of P. aeruginosa via a released metabolite - Tony-Odigie, Andrew; Dalpke, Alexander; Boutin, Sébastien; Yi, Buqing (Microbiological research, 2024)
In cystic fibrosis (CF), Pseudomonas aeruginosa infection plays a critical role in disease progression. Although multiple studies suggest that airway commensals might be able to interfere with pathogenic bacteria, the role of the distinct commensals in the polymicrobial lung infections is largely unknown. In this study, we aimed to identify airway commensal bacteria that may inhibit the growth of P. aeruginosa. Through a screening study with more than 80 CF commensal strains across 21 species, more than 30 commensal strains from various species have been identified to be able to inhibit the growth of P. aeruginosa. The underlying mechanisms were investigated via genomic, metabolic and functional analysis, revealing that the inhibitory commensals may affect the growth of P. aeruginosa by releasing a large amount of acetic acid. The data provide information about the distinct roles of airway commensals and provide insights into novel strategies for controlling airway infections.